Polymorphisms of the calpain and calpastatin genes in the Colombian creole Hartón del Valle cattle - Lenis, Claudia (2018)
The objective of the present work was to characterize the simple nucleotide polymorphism 316 and 4751 of the CAPN and 2959 gene and CAST1 of the CAST gene in the Colombian creole breed Hartón del Valle. A total of 126 individuals were genotyped by PCR-RFLP for the four loci. All markers were polymorphic. The CC genotype of the CAPN-316 locus and the heterozygote in the other three loci were more frequent. The frequencies of the alleles positively associated with meat quality were C = 21.8 ± 17.5% in CAPN-316, C = 48.4 ± 10.1% in CAPN-4751, T = 52.5 ± 11.4% in CAST-1 and A = 65.1 ± 15.5% in CAST-2959. In all the loci the Ho (0.599 ± 0.248) was higher than the He (0.410 ± 0.081) with negative values of FIS and FIT and with deviations of EHW only in CAPN-4751. The FST value was 0.048 (p<0.05) and the AMOVA showed that the variation in these loci was mostly due to individuals (97%). This may be indicative that this breed has a genetic predisposition for meat production of better quality.